I would like to reduce this statement:$$ P \veebar (P \implies B) $$ using only $\neg$, $\land$ I've found this solution but I don't know if I'm wrong: $$\neg(P \land B)$$ Because the book proposes this one using XOR: $$\neg P \veebar (P \land \neg B)$$ Is there any errors or things by which I should do the same?

Exercise 1.8-4 p.16 from Analisi matematica vol.1 by Enrico Giusti

  • $\begingroup$ What your book suggests is only a hint, not a solution. The one you have arrived at is correct, see WolframAlpha. $\endgroup$ – dtldarek May 8 '14 at 11:39
  • $\begingroup$ @dtldarek thanks for the link! in fact is with all the others solutions at the end of the chapters, maybe the author miss this solution... $\endgroup$ – G M May 8 '14 at 11:44

That's right. To check, let's unpack the initial formula:

$$P \oplus (P \rightarrow B)$$

$$P \oplus (\lnot P \lor B)$$

$$(P \lor (\lnot P \lor B))\land \lnot(P \land (\lnot P \lor B))$$

$$(\top \lor B)\land \lnot(P \land (\lnot P \lor B))$$

$$\top\land \lnot(P \land (\lnot P \lor B))$$

$$\lnot(P \land (\lnot P \lor B))$$

$$(\lnot P \lor \lnot(\lnot P \lor B))$$

$$(\lnot P \lor (P \land \lnot B))$$

$$(\lnot P \lor P) \land (\lnot P \lor \lnot B)$$

$$\top \land (\lnot P \lor \lnot B)$$

$$(\lnot P \lor \lnot B)$$

Which, once De Morganed, is equivalent to your solution:

$$\lnot(P \land B)$$


Writing out the truth tables for both we obtain the following:

P   B  (P⟹B)  [P⊻(P⟹B)]  ¬(P∧B)
0   0     1       1         1
0   1     1       1         1
1   0     0       1         1
1   1     1       0         0

Since all rows match here, it follows that your solution is correct.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.